Early detection of injuries in leaves of Clusia hilariana Schltdl. (Clusiaceae) caused by particulate deposition of iron - Rocha,Diego Ismael (2014)
This study aims to evaluate the prognostic value of microscopic parameters of asymptomatic leaves of Clusia hilariana Schltdl. subjected to particulate deposition of iron (2.14 mg cm-2 day-1) for 45 consecutive days. Samples of young and expanded leaves without symptoms were collected and subjected to light and scanning electron microscopy techniques. The height of the epidermal cells on both surfaces of the leaf and the thickness of the hypodermis, the chlorophyll parenchyma, and the leaf blade were measured. Micromorphological injury occurred in the abaxial surface of young leaves and on both surfaces of expanded leaves. Erosion of the epicuticular wax and cuticle rupture were frequent on the adaxial surface, while on the abaxial surface of both leaves there was a loss of sinuosity on the anticlinal wall of the epidermal cells, stomatal deformity and obstruction. Micromorphometric alterations were seen in all leaf tissues except in the height of epidermic cells, probably due to the thick cuticle and prominent cuticular flanges. The highest difference in thickness of the leaf blade was seen in young leaves of plants subjected to SPMFe, indicating greater sensibility to particulate iron in comparison to the expanded leaves. The micromorphological and micromorphometric alterations in the leaf blade of Clusia hilariana Schltdl. showed the prognostic potential of these tools on the evaluation of impacts caused by the deposition of particulate matter, especially in the 'Restinga' natural vegetation, where the exposure is increasing due to the presence of iron ore industry in their surroundings.